Penerapan model pembelajaran ARIAS untuk meningkatkan kemampuan penalaran matematis mahasiswa pada mata kuliah analisa real - Arfatin Nurrahmah; Abdul Karim (Math Didactic: Jurnal Pendidikan Matematika, 2018)
The purpose of this research is to know the application of model learning ARIAS in real analysis and knowing students ' mathematical reasoning ability improvement on real analysis. The research method used is the class action Research (PTK) conducted collaboratively and these forces cycle. This research consists of two cycles, each cycle consists of four stages, namely, the Act of planning, analysis, and reflection. The subject of research is the 6th semester students of mathematics education UNINDRA PGRI academic year 2017/2018 a number of 30 persons. To check the validity of the data, the researchers used a system of triangulation, i.e. one way in collecting and summing up the data with the results of observations of the three parties, namely: student, researcher and observer. The results of this research is the application of the model of learning can improve the capability of reasoning ARIAS mathematically students on real analysis. It can be seen from the increase in the average value of mathematical reasoning ability tests on the research introduction to cycle II. Preliminary tests at an average of mathematical reasoning ability is 60.50, on average I cycle the ability of mathematical reasoning is 73.07, cycle II average mathematical reasoning ability has increased into 82.43.